Heat shock protein 27 immune complex altered signaling and transport (ICAST): Novel mechanisms of attenuating inflammation. Issue 11 (4th September 2020) - Shi, Chunhua; Deng, Jingti; Chiu, Michael; Chen, Yong‐Xiang; O'Brien, Edward R.
Abstract: Blood levels of heat shock protein (HSP27) and natural IgG auto‐antibodies to HSP27 (AAbs) are higher in healthy controls compared to cardiovascular disease patients. Vaccination of mice with recombinant HSP25 (rHSP25, murine ortholog of human rHSP27) increased AAb levels, attenuated atherogenesis and reduced plaque inflammation and cholesterol content. We sought to determine if the HSP27 immune complex (IC) altered MΦ inflammation signaling (Toll Like Receptor 4; TLR4), and scavenger receptors involved in cholesterol uptake (SR‐AI, CD‐36). Combining a validated polyclonal IgG anti‐HSP27 antibody (PAb) with rHSP27 enhanced binding to THP‐1 MΦ cell membranes and activation of NF‐κB signaling via TLR4, competing away LPS and effecting an anti‐inflammatory cytokine profile. Similarly, adding the PAb with rHSP27 enhanced binding to SR‐AI and CD‐36, as well as lowered oxLDL binding in HEK293 cells separately transfected with SR‐AI and CD‐36, or THP‐1 MΦ. Finally, the PAb enhanced the uptake and internalization of rHSP27 in THP‐1 MΦ. Thus, the HSP27 IC potentiates HSP27 cell membrane signaling with receptors involved in modulating inflammation and cholesterol uptake, as well as HSP27 internalization. Going forward, we are focusing on the development of HSP27 Immune Complex Altered Signaling and Transport (ICAST) as a means of modulating inflammation.